Ag nanocubes decorated 1T-MoS2 nanosheets SERS substrate for reliable and ultrasensitive detection of pesticides. (December 2020) - Tegegne, Wodaje Addis; Su, Wei-Nien; Tsai, Meng-Che; Beyene, Agaje Bedemo; Hwang, Bing-Joe
Highlights: A novel and ultrasensitive 1T-MoS2 /AgNCs SERS substrate for pesticide detection was developed. The SERS enhancement factor of 1T-MoS2 /AgNCs nanocomposite was 1.78 × 10 7 with LOD of 1 pM for R6G. The detection limit (LOD) of thiram and thiabendazole were down to 0.15 ppb and 10 ppb, respectively. The SERS substrate obtains excellent reproducibility (RSD = 9.46%) and stability for 2 months. Abstract: Surface-enhanced Raman scattering (SERS) is a rapid and sensitive analytical technique for detecting fingerprint structures of analyte at low concentrations. However, the lack of uniform and stable substrate limits its wide applications. Here, we demonstrate a novel 1T-MoS2 /AgNCs nanocomposite SERS substrate fabricated on a flexible filter paper for sensitive analysis of pesticide residues in apple fruit. The 1T-MoS2 nanosheets were synthesized by hydrothermal method and subsequently decorated with AgNCs. Importantly, the MoS2 nanosheets form a scaffold that physically holds the AgNCs, resulting in the 1T-MoS2 /AgNCs for the adsorption of more target analytes. More importantly, the fibrous structure of the filter paper endows excellent sample collection efficiency. Interestingly, the substrate has remarkable SERS activity attributed to the synergistic effects of (i) the high electromagnetic enhancement generated from the plasmonic AgNCs, and (ii) charge transfer between the MoS2 nanosheets and the target molecules. The results showed that 1T-MoS2 /AgNCs nanocomposite substrate achieved a record enhancement factor (AEF = 1.78 × 10 7 ), a low detection limit (LOD) of 10 −12 M, and good reproducibility (RSD = 9.46%) for R6G compared to the other substrates. Also, the SERS substrate is capable of label-free detection of thiram (TRM) and thiabendazole (TBZ) pesticides in real apple juice and peel. The LOD of thiram and thiabendazole were down to 0.15 ppb and 10 ppb, respectively. As a proof-of-concept application, multi-component detection of a mixture of TRM and TBZ was successfully analyzed. Thus, 1T-MoS2 /AgNCs nanocomposite SERS substrate is promising for the ultrasensitive and label-free analysis of diverse pesticide biomarkers in real samples. Graphical abstract: Image, graphical abstract